Associations of lipid levels susceptibility loci with coronary artery disease in Chinese population - Wang, Xue-bin (Lipids Health Dis, 2015)
BACKGROUND: Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) that were associated with blood lipid levels in Caucasians. This study investigated whether these loci influenced lipid levels and whether they were associated with the risk of coronary artery disease (CAD) and its angiographic severity in Chinese population. METHODS: Six SNPs were genotyped in 1100 CAD cases and 1069 controls using the high-resolution melting (HRM) method. Coronary atherosclerosis severity was assessed by the vessel scores and the Gensini scoring system. RESULTS: Among the 6 SNPs and the genetic risks scores (GRS), the minor alleles of HNF1A rs1169288 (odd ratio (OR) = 1.18, 95 % confidence interval (CI) 1.05–1.33, P = 0.006) and MADD-FOLH1 rs7395662 (OR = 1.20, 95 % CI 1.07–1.36, P = 0.002) as well as the GRS (P = 1.06 × 10(-5)) were significantly associated with increased risk of CAD after false discovery rate (FDR) correction. The vessel (P = 0.013) and Gensini scores (β = 0.113, P = 0.002) differed among CAD patients with different SNP rs1169288 C > T genotypes. The multiple linear regression analyses using an additive model revealed that the minor allele C of SNP rs1169288 (β = 0.060, P = 0.001) and the GRS (β = 0.033, P = 3.59 × 10(-4)) were significantly associated with increased total cholesterol (TC) levels, the minor allele A of SNP rs7395662 (β = -0.024, P = 0.007) and the GRS (β = -0.013, P = 0.004) were significantly associated with decreased high-density lipoprotein cholesterol (HDL-c) levels. CONCLUSIONS: The present study demonstrated that SNPs rs1169288, rs7395662 and the GRS were significantly associated with lipid levels and the risk of CAD in Chinese population. Furthermore, the allele C of SNP rs1169288 increased the odds of coronary atherosclerosis severity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12944-015-0079-1) contains supplementary material, which is available to authorized users.